2017
DOI: 10.1007/s00170-017-0796-x
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior of chromium nitride coating in dry condition at lower sliding velocity and load

Abstract: The wear behavior of the chromium nitride (CrN) coating on piston ring material against liner material was investigated under dry conditions at room temperatures. Cat iron alloy, widely used in manufacturing of piston rings and cylinder liners, further it was coated by physical vapour deposition method. Wear tests were carried out on a Pin on Disc tribometer, Simultaneous effect of sliding velocities (0.3, 0.4, 0.6 & 0.8 m/s) and corresponding loads (10, 20, 30 & 40 N) on wear rate, friction coefficient and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…Cathode power was set at 2,500-2,700 W and pulse frequency was adjusted to form nitride phase of chromium. Detail x-ray diffractometry (XRD) analysis of the coatings were carried out as reported in our previous corresponds (Singh et al, 2017) and confirmed that the coatings structure is mainly face centred cubic (FCC) CrN with a trace of hexagonal CrN along (200) and (111) preferential orientation. Morphology of the coating as well as elemental analysis is shown in Figure 1 .…”
Section: Coating Characterisationsupporting
confidence: 72%
“…Cathode power was set at 2,500-2,700 W and pulse frequency was adjusted to form nitride phase of chromium. Detail x-ray diffractometry (XRD) analysis of the coatings were carried out as reported in our previous corresponds (Singh et al, 2017) and confirmed that the coatings structure is mainly face centred cubic (FCC) CrN with a trace of hexagonal CrN along (200) and (111) preferential orientation. Morphology of the coating as well as elemental analysis is shown in Figure 1 .…”
Section: Coating Characterisationsupporting
confidence: 72%
“…The FISCHERSCOPE HM2000 is an automated nano-indentation measuring system has been used to perform indentation test method according to ASTM standard E2546.The hardness of the upper layer of the CrN coating was 681.58 HV, examined at 300 mN/20 s.The detailed structure and phase analysis has been examined with the help of X-ray diffractometry (XRD) of the CrN coatings, which was carried out as reported in our previous corresponds at [ 11 ] and confirmed that the structure of the coating is mainly face-centered cubic (FCC) CrN with a trace of hexagonal CrN along (200) and (111) preferential orientation. The average-based parameters were obtained to examine the surface roughness of the coating in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…It is actually cast iron whose structure lies in the metal matrix and consists of graphite lamellae. The improvement of wear-resistant properties of a cast iron piston ring-cylinder liner pair of an internal combustion engine can exert a significant influence on maintaining service properties, extending service life, and reducing the repair costs [22,23,24].…”
Section: Methodology Applied In Analysing the Chemical Composition Ofmentioning
confidence: 99%